COMPLEX RECOVERY AFTER ISCHEMIC STROKE: MANUAL THERAPY AND DIET THERAPY - Hovorun, D.; Horoshko, V. I. (Rehabilitation and Recreation, 2022)
The article provides a theoretical analysis and generalization of the use of methods of manual therapy and dietetics for patients with ischemic stroke. Rather dangerous situation has developed in Ukraine, related to the consequences of a stroke. Unlike many other developed countries, where the disease ranks third among the causes of mortality, in our country it has significantly surpassed oncology and is in second place. The purpose of the study is theoretical substantiation of the use of manual therapy and dietetics in ischemic stroke. Research material and methods. One of the well-known rehabilitation approach is manual therapy, the effect of which is aimed at treating the musculoskeletal system and internal organs using the mechanical action of hands. This practice, which is used by specialists to help restore limb function in people with neurological diseases, was developed for use in stroke patients. Diet therapy is also a very important method of recovery. A properly prescribed diet is the basis for restoring the activity of the brain and the whole body after a stroke. The nutrition program should take into account the physiological features of the human body and the degree of damage to the patient's brain. Research results. The results of the study showed that manual therapy for ischemic stroke improves the movement capabilities of the affected area. Using manual therapy, joint mobility is restored, muscle contracture is weakened, coordination of movements is improved, and muscle condition is improved. Diet therapy after a stroke should consist of high-quality and nutritious products, the sources of which are vitamins, fats, acids, micro- and macroelements, etc. Also, proper nutrition should be aimed at restoring the body and preventing a repeat stroke or the development of diseases of other organs and systems. Conclusions: Manual therapy and diet therapy are effective recovery methods for ischemic stroke. The use of these methods makes it possible to speed up the process of a person's return to his usual way of life.